“Who Are You Going to Call?” Network Activation in Creative Idea Generation and Elaboration - Mannucci, Pier Vittorio; Perry-Smith, Jill E. (Academy of Management Journal, 2022)
Considering creativity as a journey beyond idea generation, scholars have theorized that different ties are beneficial in different phases. As individuals usually possess different types of ties, selecting the optimal ties in each phase and changing ties as needed are central activities for creative success. We identify the types of ties (weak or strong) that are helpful in idea generation and idea elaboration and, given this understanding, whether individuals activate ties in each phase accordingly. In an experimental study of individuals conversing with their ties, we provide evidence of the causal effects of weak and strong ties on idea generation and idea elaboration. We also find that individuals do not always activate ties optimally and identify network size and risk as barriers. Our results in a series of studies reveal that individuals with large networks, despite providing more opportunity to activate both strong and weak ties, activate fewer weak ties and are less likely to switch ties across phases than individuals with smaller networks, particularly when creativity is perceived as a high-risk endeavor. Finally, we find that activating the wrong ties leads to either dropping creative ideas or pursuing uncreative ones.